All Days 2011
DOI: 10.2118/146348-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Borehole to Surface Electromagnetic Survey in KSA: Reservoir Mapping and Monitoring at a New Scale

Abstract: The first Borehole to Surface Electromagnetic (BSEM) pilot field survey in the Kingdom of Saudi Arabia (KSA) was successfully executed to identify oil and water bearing reservoir layers in a carbonate oilfield water injection zone. Maximizing recovery factor by means of detailed mapping of hydrocarbon accumulations in the reservoirs is a key requirement for oil producing companies. This mapping is done routinely by accurate measurements of fluid distribution at the wells' locations, but a knowledge gap exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…We further assumed that for each update step, the crosswell imaging was performed sequentially for the individual wells during a time frame of 1 to 2 months and therefore does not require a total halt of the field production. On the basis of a sensitivity analysis, we could conclude that the temporal differences over which the EM and seismic surveys are conducted only marginally affect the signals, and the data were history-matched at the same UT (Schlumberger Imaging Services Report 2009Marsala et al 2011;Schlumberger 2013). Attenuation effects for both crosswell EM and seismic imaging were taken into account, as outlined in the Full-Wave Acoustic-Wave Propagation Method and Full-Wave EM Method sections.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further assumed that for each update step, the crosswell imaging was performed sequentially for the individual wells during a time frame of 1 to 2 months and therefore does not require a total halt of the field production. On the basis of a sensitivity analysis, we could conclude that the temporal differences over which the EM and seismic surveys are conducted only marginally affect the signals, and the data were history-matched at the same UT (Schlumberger Imaging Services Report 2009Marsala et al 2011;Schlumberger 2013). Attenuation effects for both crosswell EM and seismic imaging were taken into account, as outlined in the Full-Wave Acoustic-Wave Propagation Method and Full-Wave EM Method sections.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In contrast, EM data showed a strong dependence on the water-saturation changes, which is consistent with Archie's relation. EM data depend strongly on the water-saturation levels in the reservoir and therefore may more easily distinguish between heavily and less heavily waterflooded reservoirs (Marsala et al 2007(Marsala et al , 2011Lien 2013) that is rather challenging with seismic techniques. Furthermore, because of the strong salt-concentration dependence of the EM signal, EM techniques are further able to distinguish between water influx from an aquifer and the water that is injected from the surface (as outlined in the 3D case) because of the significant salt-concentration difference between the two fluids.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…To better monitor movements of hydrocarbon fluid lying between wells at a reservoir scale, fluid-saturation surveys based on cross-well EM induction tomography have been performed Wilt et al, 1995;DePavia et al, 2008;Wilt, Donadille, AlRuwaili, Ma, & Marsala, 2008;Marsala et al, 2008. Surface-to-borehole EM uses an array of borehole receivers and a movable surface source, Pardo, Torres-Verdín, Marsala et al, 2011). The cross-well EM induction tomography approach produces a resistivity distribution between wells and offers a better resolution than surface seismic surveys .…”
Section: Cross-well Electromagnetic Tomography In Hydrocarbon Reservomentioning
confidence: 99%
“…The specificity of borehole to surface EM (BSEM), in respect to crosswell EM (Xwell EM), is that BSEM requires only one surveyed well to obtain an areal map of fluid distribution of a reservoir target layer, kilometers away from the transmitting well (up to 4 km, as demonstrated in Saudi Arabian pilots, Marsala et al 2011 and2013a). Xwell EM, on the contrary, allows higher resolution results, but it is limited to cross sections between two or more wells, close enough for EM propagation: about 1 km in open holes, less in cased holes (Marsala et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The BSEM technology was first employed in the ex-USSR at the end of the last millennium and has been extensively improved in recent years in China, leading to positive field deployments and resulting in a commercial protocol, subsequently being developed and introduced by BGP (He et al 2012). Successful pilot studies of BSEM have been reported by Saudi Aramco, producing resistivity and IP images of oil-water contact at reservoir depth (Marsala et al 2011).…”
Section: Introductionmentioning
confidence: 99%